Determinasi Transparansi, Akuntabilitas dan Partisipasi Masyarakat Terhadap Pengelolaan Dana Desa - Victoria Ari Palma Akadiati; Alfalink Intan Agustin; Matheus Edwin (Jurnal Humanipreneur, 2023)
Research in Gunung Pasir Jaya Village, Sekampung Udik District, East Lampung Regency regarding the management of village funds uses the variables of transparency, accountability, and participation. The sample are 369 respondents, namely the local village community. Using method is purposive sampling. In this study the data is collected through the distribution of questionnaires by hypothesis testing using multiple linear regression analysis. The results shows that transparency, accountability and community participation had positive and significant impact to management of village funds. This shows that there is a mutually influencing relationship between the transparency principle (openness) which related to the implementation of village government accountability (responsibility) for management of village funds.